Kombinasi Alat Berat pada Pekerjaan Pemindahan Tanah Dan Galian pada Pembangunan Jalan Jalur Lintas Selatan Lot 3 Pantai Serang – Sumbersih - Septiono, Wisnu Panji; Syahputra, Aldy; Wibisana, Hendrata; Putri, Karina Meilawati Eka (Jurnal Talenta Sipil, 2025)
The construction of roads is one of the key aspects to support economic growth and facilitate community mobility. A crucial stage in this project is the earthmoving and excavation work, which requires proper heavy equipment planning to achieve efficiency in terms of time, cost, and quality. This analysis aims to evaluate the optimal combination of heavy equipment for the construction project of the South Coastal Road (JLS) Lot 3 Pantai Serang – Sumbersih, focusing on excavation and earthmoving tasks. The project faces complex geographical challenges, such as hilly terrain and varying soil types, which necessitate the use of suitable heavy equipment to optimize productivity. Using a quantitative approach, data collection, documentation studies, and interviews were conducted. The collected data were then analyzed using productivity calculation formulas for heavy equipment to identify the most efficient combination of heavy machinery. The results show that a combination of heavy equipment consisting of 1 Kobelco SK200 excavator, 1 Kobelco SK200 excavator, 4 dump trucks, and a bulldozer can improve work efficiency and reduce the required time and costs. Hence, Combination 1 was selected as the most optimal choice for excavation and earthmoving work in the JLS Lot 3 Pantai Serang – Sumbersih road construction project, achieving a total duration of 15,730 hours and a cost of IDR 25,837,774,442.